DAMPING OF VIBRATIONS IN INTERCHANGE POWER - G. M. Pavlov; H. T. Rishague (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers damping of vibrations in interchange power of interconnecting transmission lines. Influence of natural and supplementary regulation parameters on the character of transient process is shown in the paper.The paper contains recommendations for elimination of maximum interchange power deviation in the transient process.